Temporal variations in the gut microbial diversity in response to high-fat diet and exercise - Saba Imdad; Byunghun So; Junho Jang; Jinhan Park; Sam-Jun Lee; Jin-Hee Kim; Chounghun Kang (Scientific Reports, 2024)
Abstract High-fat diet-induced obesity is a pandemic caused by an inactive lifestyle and increased consumption of Western diets and is a major risk factor for diabetes and cardiovascular diseases. In contrast, exercise can positively influence gut microbial diversity and is linked to a decreased inflammatory state. To understand the gut microbial variations associated with exercise and high-fat diet over time, we conducted a longitudinal study to examine the effect of covariates on gut microbial diversity and composition. Young mice were divided into four groups: Chow-diet (CHD), high-fat diet (HFD), high-fat diet + exercise (HFX), and exercise only (EXE) and underwent experimental intervention for 12 weeks. Fecal samples at week 0 and 12 were collected for DNA extraction, followed by 16S library preparation and sequencing. Data were analyzed using QIIME 2, R and MicrobiomeAnalyst. The Bacteroidetes-to-Firmicutes ratio decreased fivefold in the HFD and HFX groups compared to that in the CHD and EXE groups and increased in the EXE group over time. Alpha diversity was significantly increased in the EXE group longitudinally (p < 0.02), whereas diversity (Shannon, Faith’s PD, and Fisher) and richness (ACE) was significantly reduced in the HFD (p < 0.005) and HFX (p < 0.03) groups over time. Beta diversity, based on the Jaccard, Bray–Curtis, and unweighted UniFrac distance metrics, was significant among the groups. Prevotella, Paraprevotella, Candidatus arthromitus, Lactobacillus salivarius, L. reuteri, Roseburia, Bacteroides uniformis, Sutterella, and Corynebacterium were differentially abundant in the chow-diet groups (CHD and EXE). Exercise significantly reduced the proportion of taxa characteristic of a high-fat diet, including Butyricimonas, Ruminococcus gnavus, and Mucispirillum schaedleri. Diet, age, and exercise significantly contributed to explaining the bacterial community structure and diversity in the gut microbiota. Modulating the gut microbiota and maintaining its stability can lead to targeted microbiome therapies to manage chronic and recurrent diseases and infections.